Long-term survival in a child with severe encephalopathy, multiple respiratory chain deficiency and GFM1 mutations - Brito, Sara; Thompson, Kyle; Campistol, Jaume; Colomer, Jaime; Hardy, Steven A.; He, Langping; Fernández-Marmiesse, Ana; Palacios, Lourdes; Jou, Cristina; Jiménez-Mallebrera, Cecilia; Armstrong, Judith; Montero, Raquel; et al. (Frontiers in Genetics, 2015)
Background: Mitochondrial diseases due to deficiencies in the mitochondrial oxidative phosphorylation system (OXPHOS) can be associated with nuclear genes involved in mitochondrial translation, causing heterogeneous early onset and often fatal phenotypes. Case report: The authors describe the clinical features and diagnostic workup of an infant who presented with an early onset severe encephalopathy, spastic-dystonic tetraparesis, failure to thrive, seizures and persistent lactic acidemia. Brain imaging revealed thinning of the corpus callosum and diffuse alteration of white matter signal. Genetic investigation confirmed two novel mutations in the GFM1 gene, encoding the mitochondrial translation elongation factor G1 (mtEFG1), resulting in combined deficiencies of OXPHOS. Discussion: The patient shares multiple clinical, laboratory and radiological similarities with the 11 reported patients with mutations involving this gene, but presents with a stable clinical course without metabolic decompensations, rather than a rapidly progressive fatal course. Defects in GFM1 gene confer high susceptibility to neurologic or hepatic dysfunction and this is, to the best of our knowledge, the first described patient who has survived beyond early childhood. Reporting of such cases is essential so as to delineate the key clinical and neuroradiological features of this disease and provide a more comprehensive view of its prognosis.